2009
DOI: 10.1063/1.3077611
|View full text |Cite
|
Sign up to set email alerts
|

Gate voltage dependence on hot carrier degradation at an elevated temperature in a device with ultrathin silicon oxynitride

Abstract: Effect of substrate hot-carrier injection on quasibreakdown of ultrathin gate oxide

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 11 publications
1
15
0
Order By: Relevance
“…Abramo et al reported that the high-energy tail was enhanced substantially both in the channel and inside the drain region [8]. Although EES stress causes severe device degradation, CHC stress results in more critical damage because CHC stress generates more interface states than EES stress [3]. However, the device degradation by EES stress increases dramatically when the channel length is scaled down due to the enhanced high-energy tail.…”
Section: Introductionmentioning
confidence: 97%
See 4 more Smart Citations
“…Abramo et al reported that the high-energy tail was enhanced substantially both in the channel and inside the drain region [8]. Although EES stress causes severe device degradation, CHC stress results in more critical damage because CHC stress generates more interface states than EES stress [3]. However, the device degradation by EES stress increases dramatically when the channel length is scaled down due to the enhanced high-energy tail.…”
Section: Introductionmentioning
confidence: 97%
“…Therefore, stress effect of EES on device lifetime should be investigated. Jo et al compared CHC (V g = V d ) and EES (V g > V d ) stresses, and reported that high-energy tail electrons caused severe damage to an nMOSFET by enhancing interface states [3]. Abramo et al reported that the high-energy tail was enhanced substantially both in the channel and inside the drain region [8].…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations